V.A.T nown; Gay Lessons; Dagyaw [videorecording] - Lazaro, Cheche (The Probe Team [episode no.303], 1994)
Summary: Documents the value added tax issue; the Gay literature course offered by U.P. Diliman English Department; the Dagyaw theater and dance company made up of high school students in Iloilo City.